Understanding Disability Throughout History Interdisciplinary Perspectives in Iceland from Settlement to 1936 - Björg Sigurjónsdóttir, Hanna; Rice, James G. (Interdisciplinary Disability Studies, 2022)
Understanding Disability Throughout History explores seldom-heard voices from the past by studying the hidden lives of disabled people before the concept of disability existed culturally, socially and administratively. The book focuses on Iceland from the Age of Settlement, traditionally considered to have taken place from 874 to 930, until the 1936 Law on Social Security (Lög um almannatryggingar), which is the first time that disabled people were referenced in Iceland as a legal or administrative category. Data sources analysed in the project represent a broad range of materials that are not often featured in the study of disability, such as bone collections, medieval literature and census data from the early modern era, archaeological remains, historical archives, folktales and legends, personal narratives and museum displays. The ten chapters include contributions from multidisciplinary team of experts working in the fields of Disability Studies, History, Archaeology, Medieval Icelandic Literature, Folklore and Ethnology, Anthropology, Museum Studies, and Archival Sciences, along with a collection of post-doctoral and graduate students. The volume will be of interest to all scholars and students of disability studies, history, medieval studies, ethnology, folklore, and archaeology.